2014
DOI: 10.1002/dvg.22835
|View full text |Cite
|
Sign up to set email alerts
|

Off‐target assessment of CRISPRCas9 guiding RNAs in human iPS and mouse ES cells

Abstract: Summary: The CRISPR-Cas9 system consists of a sitespecific, targetable DNA nuclease that holds great potential in gene editing and genome-wide screening applications. To apply the CRISPR-Cas9 system to these assays successfully, the rate at which Cas9 induces DNA breaks at undesired loci must be understood. We characterized the rate of Cas9 off-target activity in typical Cas9 experiments in two human and one mouse cell lines. We analyzed the Cas9 cutting activity of 12 gRNAs in both their targeted sites and~90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 39 publications
1
34
0
1
Order By: Relevance
“…Ce problème a cependant été atténué récemment [14]. En principe, 20 paires de bases (pb) sont plus que suffisantes pour être spécifiques d'un site cible unique dans le génome humain.…”
Section: Coupures Hors Cibleunclassified
“…Ce problème a cependant été atténué récemment [14]. En principe, 20 paires de bases (pb) sont plus que suffisantes pour être spécifiques d'un site cible unique dans le génome humain.…”
Section: Coupures Hors Cibleunclassified
“…Further studies confirmed the absence of nonspecific activity by screening for cleavage activity at the most likely predicted off-target sites based on sequence homology to the guide RNA sequence [35,36,77]. Moreover, upon screening 624 and 717 potential off-target sites for 12 sgRNA in 293FT cells and iPSCs, respectively, a total of three sites were identified as being associated with two sgRNAs only [87]. On the other hand, Xu et al [138] showed clear off-target activity at seven out of 10 sites after targeting Intron 2 of the HBB gene, and reported a comparable level of off-target activity in 293FT cells and iPSCs.…”
Section: Evidence For Dna Repair At Off-target Sites In Ipscsmentioning
confidence: 68%
“…In the context of this thesis, it is important to note that pluripotent stem cells adopt an open chromatin structure that differs from that of somatic cells [86], implying that iPSCs may have a higher propensity for off-target activity. Surprisingly, therefore, off-target Cas9 activity in iPSCs was reported to be low [87] or non-existent [88,89].…”
mentioning
confidence: 99%
See 2 more Smart Citations